Epigenetics and its role in effecting agronomical traits - Gupta, Chainika; Salgotra, Romesh K. (Frontiers in Plant Science, 2022)
The climate smart crop varieties with better adaptation to the climate change, is the need of the hour to feed the growing population. Hence, one of the most important challenges in agriculture research is to design a high yielding crop variety with improved agronomic traits. Agronomic traits are vital for yield potential and resistance to adverse conditions, which benefits the farmer in the long run. The majority of agronomic traits are quantitative and are subject to intricate genetic control, obstructing crop improvement. Plant epibreeding is the utilization of epigenetical variation for crop development, has a wide range of applications in the field of crop improvement. Epigenetics is defined as the heritable changes in gene expression that are not mediated by changes in the underlying DNA sequence but caused by DNA methylation, histone post-translational modifications and RNA interference (RNAi). These epigenetic changes are known to influence gene expression by changing the chromatin state, which underpins plant development and shapes phenotypic plasticity in response to external and internal inputs. In addition to DNA sequence variation, epigenetic alterations may aid breeding by providing valuable markers and allowing the use of epigenome diversity to forecast plant performance and boost final crop yield. In this chapter emphasis has been given for summarizing the role of epigenetic changes in epibreeding for crop improvement.